Fault mechanics and transport properties of rocks : a festschrift in honor of W.F. Brace - Evans, Brian (James Brian); Wong, Teng-fong; Brace, W. F. (William F.) (International geophysics series ;, 1992)
This festschrift, compiled from the symposium held in honor of W.F. Brace, is a timely overview of fault mechanics and transport properties of rock. State-of-the-art research is presented by internationally recognized experts, who highlight developments in this contemporary area of study subsequent to Bill Brace's pioneering work.